Clinical, endocrinological, and molecular characterization of Kallmann syndrome and normosmic idiopathic hypogonadotropic hypogonadism: a single center experience - Sun-Jeong Shin; Yeonah Sul; Ja Hye Kim; Ja Hyang Cho; Gu-Hwan Kim; Jae Hyun Kim; Jin-Ho Choi; Han-Wook Yoo (Korean Society of Pediatric Endocrinology, 2015)
PurposeIsolated gonadotropin-releasing hormone (GnRH) deficiency (IGD) is classified as Kallmann syndrome (KS) with anosmia and normosmic idiopathic hypogonadotropic hypogonadism (nIHH). This study was undertaken to investigate the clinical, endocrinological, and molecular characteristics in Korean patients with KS and nIHH.MethodsTwenty-six patients from 25 unrelated families were included. Their clinical, endocrinological, and radiological findings were analyzed retrospectively. Mutation analysis of the GNRH1, GNRHR, KISS1, KISS1R, PROK2, PROKR2, TAC3, TACR3, FGF8, FGFR1, and KAL1 genes was performed in all patients. CHD7 and SOX10 were analyzed in patients with CHARGE (Coloboma, Heart defects, choanae Atresia, Growth retardation, Genitourinary abnormality, Ear abnormality) features or deafness.ResultsOf the 26 patients, 16 had KS and 10 had nIHH. At diagnosis, mean chronologic age was 18.1 years in males and 18.0 years in females; height SDS were -0.67±1.35 in males, -1.12±1.86 in females; testis volume was 2.0±1.3 mL; and Tanner stage was 1.5. There were associated anomalies in some of the KS patients: hearing loss (n=6) and congenital heart disease (n=4). Absence or hypoplasia of the olfactory bulb/sulci was found in 84.62% of patients with KS. Molecular defects in KAL1, SOX10, and CHD7 were identified in 5 patients from 4 families (16.0%, 4/25 pedigrees). After sex hormone replacement therapy, there were improvement in sexual characteristics and the sexual function.ConclusionThis study described the clinical, endocrinological, and molecular genetic features in IGD patients in Korea. Although the mutation screening was performed in 10 genes that cause IGD, molecular defects were identified in relatively small proportions of the cohort.